2001
DOI: 10.1590/s0100-06832001000300022
|View full text |Cite
|
Sign up to set email alerts
|

Resistência do solo à penetração e desenvolvimento do sistema radicular do milho (Zea mays) sob diferentes sistemas de manejo em um Latossolo Roxo

Abstract: RESUMOAs modificações estruturais causadas no solo pelos diferentes sistemas de manejo podem resultar em maior ou menor compactação, que poderá interferir na densidade do solo, na porosidade, na infiltração de água no solo e no desenvolvimento radicular das culturas. Assim, este trabalho teve como objetivo estudar, em condições de campo, os efeitos da estrutura, umidade e resistência do solo à penetração no desenvolvimento do sistema radicular do milho (Zea mays), sob sistema convencional (aração mais grade ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
36

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 19 publications
3
29
0
36
Order By: Relevance
“…In the MCH system, the RP values were highest in the layer 0.40-0.55 m, with values above 4.0 MPa, classified as high and very high, exceeding the critical level (Tavares Filho et al, 2001;Llanillo et al, 2006). However, even though the values were highest in this layer, no significant resistance to sugarcane root growth was observed in these systems, which would cause a restrictive effect to yield increases.…”
Section: Resultsmentioning
confidence: 87%
“…In the MCH system, the RP values were highest in the layer 0.40-0.55 m, with values above 4.0 MPa, classified as high and very high, exceeding the critical level (Tavares Filho et al, 2001;Llanillo et al, 2006). However, even though the values were highest in this layer, no significant resistance to sugarcane root growth was observed in these systems, which would cause a restrictive effect to yield increases.…”
Section: Resultsmentioning
confidence: 87%
“…Assim, são necessários mais estudos sobre a viabilidade do cultivo de batata-doce sob preparo reduzido do solo, visto que a prática do plantio direto em longo período de tempo favorece os atributos físicos do solo, tornando-os mais adequados ao desenvolvimento vegetal que o plantio convencional, conforme verificado por Tavares Filho et al (2001), em latossolo vermelho argiloso, com plantio direto sendo realizado há mais de 20 anos.…”
Section: Resultsunclassified
“…There was no alteration in the soil structure, with predominance of compact, low porosity units (Δ), with a predominantly cracked (F) (50 %) structure in both profiles, be it sole maize or maize/jack bean intercropping (Figure 2). When evaluating resistance to maize root penetration in a red clay Oxisol (Latossolo Roxo argiloso), Tavares Filho et al (2001) found a compact layer caused by the use of heavy machinery between the volumes of loose (L) and continuously compact (CΔ) soil, which hampered root penetration. Thus, according to these authors, the structural modifications seem to be more restrictive for the root system development in the conventional system, due to the presence of the CΔ structure, which characterizes a very compact soil volume.…”
Section: Resultsmentioning
confidence: 99%